Clinical and Experimental Evaluation of the Effectiveness of «Soft-Start» Polymerization in Dental Composite Restoration - Timur V. Melkumyan, PhD, ScD; Kamola D. Makhamadaminova; Erkin Kh. Kamilov (International Journal of Biomedicine, 2012)
The clinical and experimental efficiency of the soft-start polymerization technique in composite restorations was studied. In this study, 57 patients between 30 and 44 years of age with secondary caries had 158 restorations done using the photo-composite material Filtek Z250. The restorations performed were distinguished into two groups, the basis of the photo-polymerization method of employed (conventional polymerization technique and «soft-start» polymerization technique). The objects of the study also included the specimens of 18 extracted teeth. The analysis of the data indicates that employing the «soft-start» polymerization technique provides better integration of the composite material to the hard tissues of the tooth. This conclusion was best demonstrated in cases where the dentin was a connecting link in the chain «substrate-hybrid layer-composite».